2001
DOI: 10.1097/00003072-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Probe–Guided Resection and Scanning with Tc-99m MIBI of a Local Recurrence of Follicular Thyroid Carcinoma

Abstract: A 30-year-old woman underwent two operations for multinodular goiter and follicular thyroid carcinoma. The residual thyroid tissue was ablated by I-131 therapy. After 7 years of follow-up, Tc-99m MIBI and I-131 scintigraphy were performed, because her serum thyroglobulin level was much higher compared with the control analysis performed in the sixth year. Tc-99m MIBI showed pathologic accumulation, which could be consistent with a local recurrence, whereas the results of I-131 scintigraphy were negative. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…proposed radio-guided surgery for the intraoperative localization and resection of locoregional, non-functioning (I-131-negative) DTC recurrences with Tc-99m MIBI. [142225] Rubello et al . reported a lesion to background ratio higher than 2.0 in all cases (mean ± SD = 3.2 ± 0.8) at operation.…”
Section: Discussionmentioning
confidence: 99%
“…proposed radio-guided surgery for the intraoperative localization and resection of locoregional, non-functioning (I-131-negative) DTC recurrences with Tc-99m MIBI. [142225] Rubello et al . reported a lesion to background ratio higher than 2.0 in all cases (mean ± SD = 3.2 ± 0.8) at operation.…”
Section: Discussionmentioning
confidence: 99%
“…Negele et al more recently presented a series of four patients and literature review, in which a similar technique was utilized [2]. Boz et al described the localization and excision of a local recurrence of follicular thyroid cancer using Tc-99m methoxyisobutyl isonitrile (MIBI) [3]. These authors demonstrated both the utility of Tc-99m MIBI for intraoperative localization and the possibility that recurrent thyroid cancer may elude detection by diagnostic I-131 whole body scanning.…”
Section: Discussionmentioning
confidence: 99%
“…The gamma-probe is resistant, portable, not too expensive and easy to use, presenting a high sensitivity and specificity, as demonstrated by the GPAS performed to remove a wide variety of tumors [3][4][5]9,10,[20][21][22][23][24][25] and sentinel-nodes [13][14][15][16][17][18][19] . In fact, its sensitivity se- ems to be greater than that of CT (Bell et al 3 : 11 of 13 patients harboring ovarian cancer underwent preoperative CT-scan, which was normal in all of them), MRI (Martinez et al 23 : one out of three patients with parathyroid disease underwent preoperative MRI and CT, being both normal) and external scintigraphy (Martin et al 4 : this procedure was normal in 11 out of 23 patients with colorectal tumor).…”
Section: Discussionmentioning
confidence: 99%
“…This technique, named by others as radioguided surgery (RGS) and by the present authors as gamma probe-assisted surgery (GPAS), was introduced into clinical practice in 1985 by Martin et al 3,4 , allowing them to promptly recognize the lesion in 28 patients harboring colorectal tumors. Using a variety of radiolabeled substances [1][2][3][4][5][6][7][8][9][10] , many authors have performed GPAS to map sentinelnodes of melanomas 13 , of breast 14 , vulvar 15 , cervical 16 , prostate 17 , penile 18 and thyroid 19 cancer, and to identify breast (the radiolabeled substance may be injected intravenously 20 and within 21 or around 22 the tumor), ovarian 3 , colorectal 4,5 , gastroenteropancreatic 10 , parathyroid 23 and thyroid 24,25 tumors and neuroblastomas 9 , with a significant successful rate.…”
mentioning
confidence: 99%